Persuasive proposals and presentations : - Pierce, Heather (McGraw-Hill, 2005)
Persuasive Proposals and Presentations shows readers how to develop a winning strategy and how to be clear, organized, and persuasive. It lays out common mistakes in strategy and offers effective advice